Health promotion and reduction of vulnerabilities: a strategy for knowledge production and (trans)formation of healthcare work, based on Ergology - Suze Rosa Sant'Ánna; Élida Azevedo Hennington (Faculdade de Medicina de Botucatu (Unesp), 2010)
The present study had the aim of reflecting on the urgency of new possibilities within healthcare settings starting from the proposal to shape an "Extended Community for Health Promotion Research". This strategy aims to contribute towards training for healthcare workers, by interlinking concepts from Yves Schwartz's ergology and its dynamic three-pole mechanism, from the perspective of going along original paths for critical reflection and requalification of healthcare work. Through this, workers can be immersed in the debate and experimentation regarding learning to share and discuss scientific and non-scientific knowledge and practices aimed at health promotion for the community. In this way, it is understood that such experiences have their chance and demands, thus becoming a possibility for knowledge production and (trans)formation of healthcare work.